Frequency of the transthyretin Val30Met mutation in the northern Swedish population. (March 2014) - Olsson, Malin; Jonasson, Jenni; Cederquist, Kristina; Suhr, Ole B.
Abstract By genotyping a large number of samples from the Northern Sweden Health and Disease Study cohort, a carrier frequency could be determined for the Skellefteå and Lycksele populations. A previous study of the amyloidogenic transthyretin mutation TTRV30M in Northern Sweden's endemic area has shown a large variation in carrier frequency and penetrance of the trait within the area. However, the estimations have been based on a small sample size within the different regions in the area and therefore, the wide variation in TTRV30M carrier frequency observed between the Lycksele and Skellefteå populations are uncertain. Based on a total of 3460 samples, the estimated overall carrier frequency in the two regions was 1.82% with a carrier frequency in the Skellefteå and Lycksele population of 1.63% and 2.02%, respectively. Thus, the previously reported extremely high frequency in the Lycksele region compared to that of the Skellefteå region could not be substantiated. However, it does not change the previous finding of a surprisingly higher carrier frequency in the population from endemic area of Northern Sweden compared to that reported from endemic areas in Portugal.